Comprehensive home based diabetic wounds care program during covid-19 pandemic in Yogyakarta - Wantonoro Wantonoro; Dwi Prihatiningsih; Endang Koni Suryaningsih Endang Koni Suryaningsih (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
Patients with COVID-19 disease who have comorbidities are strongly correlated with increased disease severity and significantly increased risk of death. Diabetes Mellitus is one of important risk factor and contributes to the severity and mortality of patients with COVID-19. Patients with chronic wounds have delayed treatment during the COVID-19 pandemic. Therefore, management of patients with chronic wounds should be improved during this pandemic. Home based wound care and education program for the family caregiver is proposed to solve the problem. Eight participants were completed this program. Evaluation of wound for each patient were conducted (at the first meeting and four- or five-months follow-up) using the diabetic foot ulcer assessment scale (DFUAS). In general, the wound depth, wound size, infection, granulation, necrotic being better compared in the first assessment. Home-based care, and education for patients and family caregiver program have benefit for diabetic wound care management during Covid-19 pandemic in this area (Yogyakarta, Indonesia). The comprehensive with multidiscipline approach are recommended for future work.